β-Patchoulene Ameliorates Water Transport and the Mucus Barrier in 5-Fluorouracil-Induced Intestinal Mucositis Rats via the cAMP/PKA/CREB Signaling Pathway - Wu, Jiazhen; Gan, Yuxuan; Luo, Huijuan; Xu, Nan; Chen, Liping; Li, Mengyao; Guan, Fengkun; Su, Ziren; Lin, Zhixiu; Xie, Jianhui; Liu, Yuhong (Frontiers in Pharmacology, 2021)
Intestinal mucositis (IM) is the main side effect observed in patients who receive cancer chemotherapy. The characteristics of ulceration, vomiting, and severe diarrhea cause patients to delay or abandon further treatment, thereby aggravating their progress. Hence, IM cannot be overlooked. β-patchoulene (β-PAE) is an active ingredient isolated from Pogostemon cablin (Blanco) Benth (Labiatae) and has shown a marked protective effect against gastrointestinal diseases in previous studies. However, whether β-PAE plays a positive role in IM is still unknown. Herein, we explore the effects and the underlying mechanism of β-PAE against 5-fluorouracil (5-FU)-induced IM in IEC-6 cells and rats. β-PAE significantly recovered cell viability, upregulated the IM-induced rat body weight and food intake and improved the pathological diarrhea symptoms. Aquaporin is critical for regulating water fluid homeostasis, and its abnormal expression was associated with pathological diarrhea in IM. β-PAE displayed an outstanding effect in inhibiting aquaporin 3 (AQP3) via the cAMP/protein kinase A (PKA)/cAMP-response element-binding protein (CREB) signaling pathway. Besides, inflammation-induced mucus barrier injury deteriorated water transport and aggravated diarrhea in IM-induced rats. β-PAE’s effect on suppressing inflammation and recovering the mucus barrier strengthened its regulation of water transport and thus alleviated diarrhea in IM-induced rats. In sum, β-PAE improved IM in rats mainly by improving water transport and the mucus barrier, and these effects were correlated with its function on inhibiting the cAMP/PKA/CREB signaling pathway.